A Cautionary Tale: Exploring Stakeholder Emotions During Curricular Change Using Group Concept Mapping. Issue 1 (13th December 2022) - Ziring, Deborah; Powell, Rhea; Vaid, Urvashi; Nord, Garrison; L'Etoile, Nathan; Herrine, Steven
Abstract: PhenomenonCurricular change is essential but challenging. Change efforts often struggle and some fail due to well-articulated challenges as well as other barriers less understood. The curricular change literature characterizes the organizational and operational features of successful change yet virtually ignores stakeholder emotions. A deeper understanding of these emotional responses during the change process could enhance participant and organizational well-being and support change success. Approach In 2019, data were collected at one large North American medical school using group concept mapping methodology, an asynchronous mixed methods approach. We sought to generate themes characterizing the emotional responses of faculty, administrative staff, and students across multiple stakeholder groups participating in the new and traditional (legacy) curricula 27 months after curricular change initiation. Participants brainstormed, sorted, and rated statements on emotional responses. Rating participants rated each statement using a Likert scale from 1 (does not resonate) to 4 (very strongly resonates) according to this prompt: "This emotional response resonates with my emotional experience during the curricular change." Multidimensional scaling and hierarchical cluster analyses were used to generate emotional profiles and compare them across stakeholders. Findings Of 335 stakeholders invited, 123 contributed to brainstorming (36.7%), 153 completed rating (45.7%) and 33 completed sorting (9.9%). Participants generated six themes of emotional responses to curricular change: enthusiastic, apprehensive, overwhelmed, missed opportunities, uncertain, and abandoned . The enthusiastic theme overall had the highest mean statement ratings while the abandoned theme had the lowest. Demographic subgroup analysis revealed new curriculum students (Class of 2021) were most enthusiastic while legacy curriculum students (Class of 2020) were more likely to feel abandoned. Overall, faculty and administrative staff were more enthusiastic than students whereas students rated the five other themes higher than faculty and administrative staff. Insights Curricular change is emotionally taxing. Students in both curricula experienced greater uncertainty, apprehension, sense of missed opportunities, and feeling overwhelmed than did faculty and administrative staff. Legacy curriculum students rated statements in the abandoned cluster highest while new curriculum students rated statements in the enthusiastic cluster highest. Given the ubiquity of curricular change which often includes a legacy cohort, medical schools embarking on this journey must carefully attend to the varied emotional responses of their different stakeholder groups. The very activities recommended by organizational change models used in medical education, such as communicating wins early and often, could alienate legacy students, creating emotional polarization. These findings suggest that tailored communication strategies are necessary during change implementation to optimize success.